Bioprospecting of marine microorganisms for the discovery of antibacterial compounds - Isolation, structure elucidation and bioactivity assessment of marine microbial natural products - Jenssen, Marte (UiT The Arctic University of Norway, 2022)
Infectious diseases have been a problem for humans since the beginning of human existence. The “golden age” of antibiotics started at the end of the 1920s, with the discovery of penicillin by Sir Alexander Fleming. This was followed by the discovery of several life-saving antibiotics. The number of new marketed antibiotics has declined, and most pharmaceutical companies are no longer working in antibiotic development. This in itself would be unproblematic, had it not been for the rapid ability of bacteria to become resistant towards previously debilitating agents. The need for new antibiotics is therefore eminent. Natural products have been important contributors for antibiotic drug discovery and development. Microorganisms have been a particularly proliferative source of antibiotics, providing us with among others the penicillins, aminoglycosides, tetracyclines and polymyxins. Most naturally derived pharmaceuticals, including antibiotics, originate from terrestrial organisms. This is mainly because the terrestrial environment historically has been easier to access compared to the marine environment below the intertidal zone. The marine environment is highly diverse, and there is still a huge biodiversity that is yet to be explored. In this project, Arctic and sub-Arctic marine bacteria and fungi were cultivated and studied for their production of natural products. The cultures were extracted and fractionated, and the fractions were tested for bioactivity, mainly focusing on antibacterial activity. Using bioactivity-guided isolation, compounds were isolated and structurally characterized. Finally, the bioactivity of the isolated compounds was broadly evaluated. In paper I, a known siderophore, serratiochelin A, was isolated from a co-culture of two bacteria, Serratia sp. and Shewanella sp. The compound was not detected in axenic cultures, indicating that cocultivation triggered production. The acid-catalyzed degradation of serratiochelin A into serratiochelin C was also observed. Serratiochelin A had weak ...